FINANSIAL USAHA PENGOLAHAN BAHAN OLAH KARET (BOKAR) DI KABUPATEN TULANG BAWANG BARAT - Dian Ika Sari; M Irfan Affandi; Achdiansyah Soelaiman (Lampung University, 2016)
The purposes of this research were to know the feasibility of bokar processing business. It was conducted in Mulyo Kencono Village, the Central of Tulang Bawang of Western Tulang Bawang Regency in April to June 2015. The research sample of 60 people were taken from 269 people of the population. Financial analysis was done by discount factor and compounding factor and then analyzed by four investment criteria: Net B/C, Gross B/C, NPV, and IRR. The results from the obtained analysis showed that Net B/C was1.58; Gross B/C was 1.08; NPV was Rp95,051,373.41; and IRR was 20 percent. The obtained four investment criteria showed that bokar processing was feasible to be continued. This research in line with the previous research on a nursery rubber, that the business had been done for business operators was feasible to be continued. In addition, analysis of the scale of venture was done by comparing the number of investment and total business revenues per year against business criteria scale based on UU RI No. 20 in the year of 2008 on micro business, small, and medium. Bokar processing business was a micro business with the level of investment during a period was Rp9,912,860.85 and revenue in a year was Rp33,664,813.13. Key words: financial, marketing, rubber